Internal governance and real earnings management - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2016)
We examine whether internal governance affects the extent of real earnings management in U.S. corporations. Internal governance refers to the process through which key subordinate executives provide checks and balances in the organization and affect corporate decisions. Using the number of years to retirement to capture key subordinate executives’ horizon incentives and using their compensation relative to CEO compensation to capture their influence within the firm, we find that the extent of real earnings management decreases with key subordinate executives’ horizon and influence. The results are robust to alternative measures of internal governance and to various approaches used to address potential endogeneity including a difference-in-differences approach. In cross-sectional analyses, we find that the effect of internal governance is stronger for firms with more complex operations where key subordinate executives’ contribution is higher, is enhanced when CEOs are less powerful, is weaker when the capital markets benefit of meeting or beating earnings benchmarks is higher, and is stronger in the post-SOX period. This paper contributes to the literature by examining how internal governance affects the extent of real earnings management and by shedding light on how the members of the management team work together in shaping financial reporting quality.